2021
DOI: 10.1097/aog.0000000000004574
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Outcomes With Systematic Treatment and Management of Postpartum Hypertension

Abstract: OBJECTIVE: To test the ability of a hospital-wide, bundled quality-improvement initiative to improve postpartum maternal blood pressure control and adherence to postpartum follow-up among patients with hypertensive disorders of pregnancy. METHODS: This quality-improvement initiative consisted of a bundle of clinical interventions including health care professional and patient education, a dedicated nurse educator, and protocols for postpartum hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Only few interventional studies have been conducted on postpartum care. Riemer et al recently demonstrated that early postpartum aerobic endurance exercise can reduce arterial stiffness, as a predictor for CVD 27 , and implementing a structured, bundled management of postpartum care after PE was shown to improve blood pressure control during the first 6 weeks after birth 28 . Hypertension is a crucial risk factor for CVD that emerges after PE and accounts for substantially increased mortality 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Only few interventional studies have been conducted on postpartum care. Riemer et al recently demonstrated that early postpartum aerobic endurance exercise can reduce arterial stiffness, as a predictor for CVD 27 , and implementing a structured, bundled management of postpartum care after PE was shown to improve blood pressure control during the first 6 weeks after birth 28 . Hypertension is a crucial risk factor for CVD that emerges after PE and accounts for substantially increased mortality 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the postpartum period, there are tools that exist to aid in minimizing these adverse outcomes. Studies have illustrated that postpartum blood pressure monitoring in patients with chronic hypertension and HDP is a sustainable and important intervention for patients in the postpartum setting ( 83 , 84 ). One tertiary care center implemented a postpartum blood pressure monitoring program that included standardized education and assisted follow-up, illustrating a dramatic increase in postpartum visit attendance (33.5% vs. 59.4%, p < 0.001) with more patients reporting blood pressures of <140/90 (39.1% vs. 18.5%, p = 0.004) ( 84 ).…”
Section: Prediction Of Preeclampsia and Related Adverse Outcomesmentioning
confidence: 99%
“…Studies have illustrated that postpartum blood pressure monitoring in patients with chronic hypertension and HDP is a sustainable and important intervention for patients in the postpartum setting ( 83 , 84 ). One tertiary care center implemented a postpartum blood pressure monitoring program that included standardized education and assisted follow-up, illustrating a dramatic increase in postpartum visit attendance (33.5% vs. 59.4%, p < 0.001) with more patients reporting blood pressures of <140/90 (39.1% vs. 18.5%, p = 0.004) ( 84 ). Importantly, when incorporating telemedicine, racial disparities in visit compliance were reduced, providing one mechanism through which health equity in the setting of postpartum care can be mitigated ( 85 ).…”
Section: Prediction Of Preeclampsia and Related Adverse Outcomesmentioning
confidence: 99%
“…Preconception care is recommended for all women with pre-existing hypertension to optimize BP control, general health and weight; assess for complications; review of medications; folic acid supplementation and patient education. 14 The guideline recommends early universal screening for HDP in all pregnant women at booking using automated/mercury BP monitors. 3 All women diagnosed to be hypertensive are offered screening for preeclampsia in first trimester by maternal characteristics, mean arterial BP measurement (MAP) and Uterine artery Pulsality Index (UTPI).…”
Section: Executive Summarymentioning
confidence: 99%